Análise proteômica diferencial da fração periplasmática de Xanthomonas citri subsp. citri: proteínas relacionadas com a indução da patogenicidade in vitro - Artier, Juliana (2010)
Citrus canker is an economically important disease that affects many citrus growing areas around the world, and there is no effective control or cure. The causative agents are bacteria from the genus Xanthomonas, recently classified as two novel species, X. citri e X. fuscans. The most virulent strain is X. citri subsp. citri (Xac). In this study, we did a differential proteomic analysis of a periplasmatic proteins enriched fraction from Xac, by comparison of the protein profiles after cellular growth in pathogenicity inducing medium (XAM1) or non-inducing medium (Nutrient Broth). We performed Bidimensional Electrophoresis (2D-PAGE) in triplicate and statistical analyses were done with the software Image Master Platinum (GE). At least 80 spots showed significant differences on protein expression (p<0.05) between the two conditions tested (induction/ non-induction) and had their proteins digested by trypsin. The peptides were analyzed by mass spectrometry (LCESI- Q-Tof) and the results were compared with proteins from genome databases using the Mascot tool. Among Xac proteins identified with higher expression in in vitro pathogenicity inducing situation, two are classified as proteins involved with Pathogenicity, Virulence, and Adaptation (in according to the genome annotation): superoxidase dismutase (XAC2386) e phosphoglucomutase (XAC3579). A highly differential spot (46), increased in the inducing condition, had their proteins identified as lytic murein transglycosilase (XACb0007) and/or transglycosylase (XAC3225), oxidoreductase (XAC1160) and DNA polymerase III subunit beta (XAC0002). The spot 46 was isolated from several 2D gels and used to produce antibody in mouse. The expressions of these proteins were analyzed by Western blot in others citrus canker genome strains, which differ from Xac in the virulence and host types. This analysis showed that proteins from the spot 46 had different expression pattern among these strains, with higher expression in Xac growing in inducing condition. We conclude that the proteomic study of proteins from periplasmic fraction is an important strategy to detect Xac proteins involved with pathogenicity and virulence, even including proteins transported outside the cell. Proteins found in this fraction could be used as biomarkers, however more experiments are still necessary.